Preserving the Quality of Fresh‐Cut Guava (Psidium guajava L.) With an Aloe Vera‐Based Multilayered Polysaccharide Edible Coating - Kamlesh S. Patel; Sonu Sharma; Prakash R. Patel; T. V. Ramana Rao; Madaraboina Venkateswara Rao (Future Postharvest and Food)
ABSTRACT Guava (Psidium guajava L.) is a nutritionally valuable fruit, but its shelf life significantly decreases once cut. Edible coatings can mitigate this issue. This study evaluated various coatings, including xanthan gum (0.25%), HPMC (0.1%), and cinnamic acid (0.1%), both individually and in combination, as well as Aloe vera gel combined with these ingredients. The quality of fresh‐cut guava slices was assessed under the storage temperature of 10°C. Coated samples showed significantly better retention of physicochemical attributes than untreated controls. Aloe vera gel, particularly when combined with HPMC (0.1%), was most effective in preserving total phenolic content, Vitamin C, DPPH activity, and sensory qualities, primarily due to its ability to limit oxygen availability and prevent oxidative degradation. The combination of Aloe vera gel, cinnamic acid, and xanthan gum also performed well across all parameters. HPMC's flexibility, odorlessness, and resistance to oils and fats enhance its effectiveness as an oxygen and aroma barrier. In conclusion, the combined use of Aloe vera gel, cinnamic acid, and xanthan gum effectively preserved the quality and extended the shelf life of fresh‐cut guava.